2013
DOI: 10.1001/jamainternmed.2013.10037
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Validation of the Good Outcome Following Attempted Resuscitation (GO-FAR) Score to Predict Neurologically Intact Survival After In-Hospital Cardiopulmonary Resuscitation

Abstract: IMPORTANCE Informing patients and providers of the likelihood of survival after in-hospital cardiac arrest (IHCA), neurologically intact or with minimal deficits, may be useful when discussing do-not-attempt-resuscitation orders. OBJECTIVE To develop a simple prearrest point score that can identify patients unlikely to survive IHCA, neurologically intact or with minimal deficits. DESIGN, SETTING, AND PARTICIPANTS The study included 51 240 inpatients experiencing an index episode of IHCA between January 1, 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(167 citation statements)
references
References 27 publications
4
159
1
3
Order By: Relevance
“…Finally, our obligation to family involves providing information and support during their time of loss. • Dependent for ADLs* 48 • Homebound* 11 • Living in SNF † 13 • Neurologic status † 13 • Altered mental status* 48 • Medical noncardiac diagnosis ‡ 13,48 • Pneumonia ‡ 11,13,48 • Hypotension* 11,48 • Renal insufficiency/failure ‡ 11,13,48 • Acute stroke † 13 • Septicemia † 13 • Respiratory insufficiency † 13 • Major trauma ‡ 13,48 • Witnessed arrest* 49 • *Associated with survival †Associated with neurological outcome ‡Associated with both survival and neurological outcome §Based on expert opinion, or data from laboratory or out of hospital arrest studies…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our obligation to family involves providing information and support during their time of loss. • Dependent for ADLs* 48 • Homebound* 11 • Living in SNF † 13 • Neurologic status † 13 • Altered mental status* 48 • Medical noncardiac diagnosis ‡ 13,48 • Pneumonia ‡ 11,13,48 • Hypotension* 11,48 • Renal insufficiency/failure ‡ 11,13,48 • Acute stroke † 13 • Septicemia † 13 • Respiratory insufficiency † 13 • Major trauma ‡ 13,48 • Witnessed arrest* 49 • *Associated with survival †Associated with neurological outcome ‡Associated with both survival and neurological outcome §Based on expert opinion, or data from laboratory or out of hospital arrest studies…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Ebell et al developed a prediction model for neurologic outcome and found that good neurologic function on hospital admission is most highly associated with a good neurologic outcome after resuscitation (able to work with minimal impairment), while trauma, stroke and age 85 or older are associated with greater impairment. 13 In children, renal failure and epinephrine infusion prior to the arrest were associated with mortality. 14 Therefore knowing the patient's history is critical.…”
Section: Clinical Features That Predict Survivalmentioning
confidence: 99%
“…Using data from over 50,000 in-hospital cardiac arrests contained in the American Heart Association's 'Get with the Guidelines' registry project, Ebell et al 159 developed a scoring system to identify patients who were unlikely to benefit from a resuscitation attempt. The Good Outcome Following Attempted Resuscitation (GO-FAR) scoring system was able to identify a cohort of patients (approximately 10% of acute admissions) who had a very low chance of a good outcome (< 1% survival with intact brain function).…”
Section: Stakeholder Engagementmentioning
confidence: 99%
“…[30][31][32][33][34][35] The authors prefer the Pittsburgh Post-Cardiac Arrest Category (PCAC), because it uses bedside assessment and testing on hospital arrival rather than historical variables, thus providing early outcome prediction and facilitating risk-adjusted decision-making for hospital-based procedures and interventions. The PCAC is a validated, early postcardiac arrest illness severity score based on initial cardiopulmonary dysfunction (Sequential Organ Failure Assessment [SOFA] score: cardiovascular and respiratory components) and neurologic examination (FOUR score: motor and brainstem components).…”
Section: Postcardiac Arrest Illness Severitymentioning
confidence: 99%